The Case Study of China Construction Bank about Fintech - Wenbo Lyu; Daliang Gao (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
With the combination of finance and technology, more and more financial companies have emerged, more and more technologies have been applied to the financial industry, and the financial technology ecosystem has also begun to take shape. However, under the circumstances of deepening financial openness, increasing risks and a strict supervision environment, China’s commercial banks are facing new challenges in the development of the industry. In the financial market, commercial banks as the main body of the market, but also the key to financing, its operation and our country’s financial market and the quality of economic development are closely linked. For a long time, China’s commercial banks have had some shortcomings in the concept of innovation and innovation ability, as well as weak asset allocation ability and slow updating of product and service varieties. In order to improve their profitability, they must change their business thinking and innovate their business model. Some commercial banks have realized the importance of financial technology in the development of the banking industry, and in order to enhance their competitiveness, they have begun the development and transformation of financial technology. Therefore, standing in the background of the development of financial technology, this paper analyzes the operating mechanism of financial technology in China’s commercial banks and discusses the transformation and upgrading of commercial banks through financial technology, which will be helpful to improve the operating conditions of banks, deepen financial services and expand the breadth of services. Firstly, the article defines the connotation of financial technology, and the boundary between it and other concepts, and then makes an in-depth analysis of the development prospect of financial technology in China and related theoretical mechanisms. And through the case study of China Construction Bank, proves that the rapid development of financial technology has improved the operation of commercial banks and made it become a new economic growth point. Finally, it is of great significance to improve the operating conditions of China’s commercial banks through the study of the management concept of commercial banks, the improvement of bank operation methods, and the enhancement of financial technology capabilities.